Constraining the Hubble constant and its lower limit from the proper motion of extragalactic radio jets. Issue 1 (15th September 2022) - Hsiao, Tiger Yu-Yang; Goto, Tomotsugu; Hashimoto, Tetsuya; Santos, Daryl Joe D; Wong, Yi Hang Valerie; Kim, Seong Jin; Raquel, Bjorn Jasper R; Ho, Simon C-C; Chen, Bo-Han; Kilerci, Ece; Lu, Ting-Yi; On, Alvina Y L; et al.
ABSTRACT: The Hubble constant ( H 0 ) is a measurement to describe the expansion rate of the Universe in the current era. However, there is a 4.4σ discrepancy between the measurements from the early Universe and the late Universe. In this research, we propose a model-free and distance-free method to constrain H 0 . Combining Friedman–Lemaître–Robertson–Walker cosmology with geometrical relation of the proper motion of extragalactic jets, the lower limit ( H 0, min ) of H 0 can be determined using only three cosmology-free observables: the redshifts of the host galaxies, and the approaching and receding angular velocities of radio jets. Using these, we propose to use the Kolmogorov–Smirnov test (K–S test) between cumulative distribution functions of H 0, min to differentiate cosmology. We simulate 100, 200, and 500 extragalactic jets with three levels of accuracy of the proper motion (μa and μr ), at 10, 5, and 1 per cent, corresponding to the accuracies of the current and future radio interferometers. We perform K–S tests between the simulated samples as theoretical distributions with different H 0 and power-law index of velocity distribution of jets and mock observational data. Our result suggests increasing sample sizes leads to tighter constraints on both power-law index and the Hubble constant at moderate accuracy (i.e. 10 and 5 per cent ), while at 1 per cent accuracy, increasing sample sizes leads to tighter constraints on power-law index more. Improving accuracy results in better constraints in the Hubble constant compared with the power-law index in all cases, but it alleviates the degeneracy.